2019
DOI: 10.1038/s41598-019-47542-5
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of the Akt1-mTORC1 Axis Alters Venous Remodeling to Improve Arteriovenous Fistula Patency

Abstract: Arteriovenous fistulae (AVF) are the most common access created for hemodialysis, but up to 60% do not sustain dialysis within a year, suggesting a need to improve AVF maturation and patency. In a mouse AVF model, Akt1 regulates fistula wall thickness and diameter. We hypothesized that inhibition of the Akt1-mTORC1 axis alters venous remodeling to improve AVF patency. Daily intraperitoneal injections of rapamycin reduced AVF wall thickness with no change in diameter. Rapamycin decreased smooth muscle cell (SMC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 43 publications
1
28
0
Order By: Relevance
“…We have previously shown that Akt1 knockout mice have reduced wall thickness after AVF creation, 16 and inhibition of the Akt1-mTORC1 axis with rapamycin resulted in thinner remodeled veins. 61 Thus, the increased outward remodeling and wall thickening that occurs during venous remodeling after activation of EphrinB2 signaling may be mediated via enhanced eNOS, Akt1, and hoc; 0 versus 5 min); P [ 0.001 (post hoc; 0 versus 15 min). n MAPK signaling; although we have previously shown the importance of the eNOS 21 and Akt1 61 pathways for venous remodeling, these pathways are not specific to EphrinB2 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that Akt1 knockout mice have reduced wall thickness after AVF creation, 16 and inhibition of the Akt1-mTORC1 axis with rapamycin resulted in thinner remodeled veins. 61 Thus, the increased outward remodeling and wall thickening that occurs during venous remodeling after activation of EphrinB2 signaling may be mediated via enhanced eNOS, Akt1, and hoc; 0 versus 5 min); P [ 0.001 (post hoc; 0 versus 15 min). n MAPK signaling; although we have previously shown the importance of the eNOS 21 and Akt1 61 pathways for venous remodeling, these pathways are not specific to EphrinB2 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous studies, the diameter of the IVC distal to the AVF site in mice with an AVF but without a stenosis also increased compared with the IVC diameter of sham-operated mice ( Fig 2, B and D ; blue vs black), both upstream and downstream of the stenosis. 8 , 10 , 17 , 18 Mice with both a stenosis and an AVF also showed a large upstream IVC diameter and smaller IVC downstream diameter, compared with mice with an AVF but without a stenosis ( Fig 2, B and D ; red vs blue). In mice with an IVC stenosis alone, the IVC diameter was similar to sham-operated mice, both upstream and downstream of the stenosis ( Fig 2, B and D ; green vs black).…”
Section: Resultsmentioning
confidence: 93%
“…In the current AV fistula model, CD44 was elevated after AV fistula creation in WT mice, and the surge was attenuated in MMP-9 −/− mice (WT CTL 0.16 ± 0.06 vs. WT AVF 0.81 ± 0.11, MMP-9 −/− CTL 0.18 ± 0.09 vs. 0.43 ± 0.04; p < 0.0001 and p = 0.0123, respectively; n = 6 in each group; Figure 7 B). In addition to CD44, the Akt and ERK phosphorylation is also linked to AV fistula stenosis [ 12 , 39 ]. Phospho-Akt was significantly upregulated after AV fistula surgery and MMP-9 deficiency ameliorated the effect (WT CTL 1.32 ± 0.26 vs. WT AVF 2.72 ± 0.26, MMP-9 −/− CTL 0.59 ± 0.06 vs. MMP-9 −/− 1.36 ± 0.17; p = 0.0006 and 0.0009 respectively; Figure 7 C).…”
Section: Resultsmentioning
confidence: 99%